Tugas Roh Kudus Dalam Misi Berdasarkan Kitab Kisah Para Rasul - Randy Frank Rouw (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2019)
This article was made with the aim of describing the duties of the Holy Spirit seen from the Book of Acts and their relation to the missionary mission. In researching this topic, the author uses a literature review of books. The results of the research related to the role of the Holy Spirit are: First, the Holy Spirit fulfills the students in the ministry. He also enabled them to witness to the name of Christ and give courage to them. Second, the Holy Spirit chooses certain people for His task. Third, the Holy Spirit leads His messengers in missionary service. Fourth, the Holy Spirit works in the church. Fifth, the Holy Spirit strengthens the disciples to witness through His faithful, steadfast and willing servants for Christ. Sixth, the Holy Spirit also fulfills Gentiles, which is evidence of equality between Jews and Gentiles. Artikel ini dibuat dengan tujuan memaparkan tugas-tugas Roh Kudus dilihat dari Kitab Kisah Para Rasul dan kaitannya dalam misi pekabaran Injil. Dalam meneliti topik ini, penulis menggunakan tinjauan kepustakaan dari buku-buku. Hasil dari penelitian kaitannya dengan peran Roh Kudus adalah: Pertama, Roh Kudus memenuhi murid-murid dalam pelayanan. Ia juga memampukan mereka untuk bersaksi bagi nama Kristus dan memberikan keberanian kepada mereka. Kedua, Roh Kudus memilih orang-orang tertentu untuk tugas-Nya. Ketiga, Roh Kudus memimpin para utusan-Nya dalam pelayanan misi. Keempat, Roh Kudus berkarya dalam jemaat. Kelima, Roh Kudus menguatkan murid-murid untuk bersaksi melalui pelayan-Nya yang setia, teguh dan rela berkorban bagi Kristus. Keenam, Roh Kudus juga memenuhi orang-orang non-Yahudi yang mana ini menjadi bukti adanya kesetaraan antara orang-orang Yahudi dan non-Yahudi.